Gender Contribution in Management of Agrforestry to Household Income in Sumbermulyo Village Banyuwangi - Joko Triwanto; Lela Afinatus Saadah; Tria Wahidiah; Ali Mahmud; Febri Arif Cahyo Wibowo (Jurnal Ilmu Ilmu Kehutanan, 2024)
Forest management as stated in the forestry law no. 41 of 1999 it is explained that forest management must be carried out in a sustainable manner in compliance with the principles of sustainable forest management. The purpose of the study was to analyze the contribution of agroforestri management activities to household income in Sumbermulyo Village, Pesanggaran District, Banyuwangi Regency. The research was conducted in November 2020 at the coordinates of 8o32'46.3"S 114o 06'35.0"E. In this study, the samples to be taken were all respondents, namely 70 people who were obtained from the number of agroforestri management communities in Sumbermulyo Village. The data analysis carried out was the sperman rank correlation test for the contribution of agroforestri management to farmers' income. Based on the results of the study, it was shown that the working time of the male sex contributed more to the management of agroforestri than the female sex. The contribution of agroforestri shows that the variables of agroforestri type, marketed selling price of agroforestri, amount of fertilizer, and production costs per harvest have a correlation with household income.